Does recipient body mass index inform donor selection for allogeneic haematopoietic cell transplantation?. (14th March 2022) - Abou‐Ismail, Mouhamed Yazan; Fraser, Raphael; Allbee‐Johnson, Mariam; Metheny, Leland; Ravi, Gayathri; Ahn, Kwang Woo; Bhatt, Neel S.; Lazarus, Hillard M.; de Lima, Marcos; El Jurdy, Najla; Hematti, Peiman; Beitinjaneh, Amer M.; et al.
Summary: It is not known whether obesity has a differential effect on allogeneic haematopoietic cell transplantation outcomes with alternative donor types. We report the results of a retrospective registry study examining the effect of obesity [body mass index (BMI) > 30] on outcomes with alternative donors (haploidentical related donor with two or more mismatches and receiving post‐transplant cyclophosphamide [haplo] and cord blood (CBU)] versus matched unrelated donor (MUD). Adult patients receiving haematopoietic cell transplantation for haematologic malignancy (2013–2017) ( N  = 16 182) using MUD ( n  = 11 801), haplo ( n  = 2894) and CBU ( n  = 1487) were included. The primary outcome was non‐relapse mortality (NRM). The analysis demonstrated a significant, non‐linear interaction between pretransplant BMI and the three donor groups for NRM: NRM risk was significantly higher with CBU compared to haplo at BMI 25–30 [hazard ratio (HR) 1.66–1.71, p  < 0.05] and MUD transplants at a BMI of 25–45 (HR, 1.61–3.47, p  < 0.05). The results demonstrated that NRM and survival outcomes are worse in overweight and obese transplant recipients (BMI ≥ 25) with one alternative donor type over MUD, although obesity does not appear to confer a uniform differential mortality risk with one donor type over the other. BMI may serve as a criterion for selecting a donor among the three (MUD, haplo and CBU) options, if matched sibling donor is not available.